Non pharmacological treatments in fibromyalgia - M. Spath; D. Buskila; M.A. Giamberardino; R. Torta; A. Marsico; R. Gorla; G. Leardini; A. Alciati; L. Altomonte; S. Stisi; F. Atzeni; F. Ceccherelli; et al. (PAGEPress Publications, 2011)
To fully answer the complex question of what modes of non pharmacological treatments are useful for fibromyalgia (FM) one should ask different layers of questions, and as with peeling layers of onions, be prepared to shed some tears. The first painful question, or layer of the onion, is related to understanding patients' complaints. Patients who experience recurrent as well as persistent physical symptoms without any objective evidence are too often classified as "psychosomatic disorders" or worse as "non disease" (see Sarzi this issue)...